Concurrent and Overlapping Surgery: Perspectives From Parents of Adolescents Undergoing Spinal Posterior Instrumented Fusion for Idiopathic Scoliosis. Issue 1 (1st January 2019) - Bryant, Jessica; Markes, Alexander; Woolridge, Tiana; Cerruti, Dede; Dzeng, Elizabeth; Koenig, Barbara; Diab, Mohammad
Abstract : Study Design: Prospective cross-sectional survey. Objective: To determine the perspectives of parents of patients undergoing posterior instrumented fusion for adolescent idiopathic scoliosis (AIS) regarding simultaneous surgery and trainee participation. Summary of Background Data: Simultaneous ("at the same time") surgery is under scrutiny by the public, government, payers, and the medical community. The objective of this study is to determine the perspectives of parents of patients undergoing posterior instrumented fusion for adolescent idiopathic scoliosis. Our goal is to inform the national conversation on this subject with real patient and family voices. Methods: A survey was prospectively administered to 31 consecutive parents of patients undergoing posterior instrumented fusion for adolescent idiopathic scoliosis at a large academic medical center. "Overlapping" was defined as simultaneity during "noncritical" parts of an operation. "Concurrent" was defined as simultaneity that includes "critical" part(s) of an operation. Participants were asked to provide levels of agreement with overlapping and concurrent surgery and anesthesia, as well as with trainee involvement. Results: On average, respondents "strongly agree" with the need to be informed about overlapping or concurrent surgery. They "disagree" with both overlapping and concurrent scheduling, and "disagree" with trainees operating without direct supervision, even for "noncritical" parts. Informing parents about the presence of a back-up surgeon or research demonstrating safety of simultaneous surgery did not make them agreeable to simultaneous scheduling. Conclusion: Parents have a strong desire to be informed of simultaneous spinal surgery and anesthesia as part of consent on behalf of their children. Their disagreement with simultaneous surgery, as well as with trainees operating without direct supervision, suggests discordance with current guidelines and practice and should inform the national conversation moving forward. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the textThis is a prospective cross-sectional survey regarding simultaneous surgery performed of parents of patients undergoing posterior instrumentation and fusion for AIS. Parents "strongly agree" with the need to be informed about simultaneous scheduling. They "disagree" with simultaneous scheduling, and "disagree" with trainees operating without direct supervision, even for "noncritical" parts.